Enrichment of trace rare earth elements from the leaching liquor of ion-absorption minerals using a solid complex centrifugal separation process. Issue 9 (28th March 2018) - Wang, Yanliang; Guo, Xiangguang; Bi, Yanfeng; Su, Jia; Kong, Weichang; Sun, Xiaoqi
Abstract : A novel solid complex centrifugal separation (SCCS) process has been developed to enrich trace rare earth (RE) elements from the leaching liquor of ion-absorption RE minerals. Abstract : A novel solid complex centrifugal separation (SCCS) process has been developed to enrich trace rare earth (RE) elements from the leaching liquor of ion-absorption RE minerals. When compared to liquid–liquid centrifugal extraction (LLCE), the proposed process employed 100% extractant without a volatile diluent for the RE enrichment process, which led to a much shorter equilibrium time of 5 min. Taking into account their ability to form solid complexes with RE ions from an aqueous phase, some alkyl phenoxy carboxylic acid derivatives, including p-tert -octylphenoxy acetic acid (POAA), iso-propanoic acid (POPA) and iso-butyric acid (POBA), were synthesized and used as the solid extractants. The SCCS process included the following steps: first, the solid extractants with a saponification degree of 80% were mixed with 0.5 g L −1 RE solution at a liquid/solid phase ratio of 200/1 to obtain the solid RE complexes. Second, the solid RE complexes were separated from the aqueous phase using a liquid/solid centrifugal separator. Finally, a high concentration of RE solution (>200 g L −1 ) was obtained by the stripping of solid RE complexes with concentrated HCl. In the SCCS process, a precipitation rate of more than 95.4% and a stripping rate of nearly 100% for RE could be achieved. Water solubilities of the as-prepared solid extractants in raffinate solution were tested to be lower than 32.8 ppm at 25 °C and the mass loss were determined as 0.6% for each cycle. The as-obtained high concentration RE solution with the purity of 96.9 wt% can be used directly as a feed solution for the next individual RE element separation.